The Use of Balanced Scorecard to Support Achievement of Business Plan in Digestive Endoscopy Center, 2013 - Murdani Abdullah; Dadang Makmun; Achmad Fauzi; Aan Santi (The Indonesian Society for Digestive Endoscopy, 2014)
Background: Digestive Endoscopy Center, Cipto Mangunkusumo Hospital was established in 2011 in which the concept was developed as center of excellence (CoE). The business plan was created based on safety and patient satisfaction, fast, accurate, quality and one stop services. 2013 is the 2nd year in Digestive Endoscopy Center business plan development and it is expected to increase in many aspects. The aim of this study is to measure the performance of business plan in Digestive Endoscopy Center.Method: This study was conducted from April-December 2013 with quantitative method and cross sectional studies on 76 subjects and also used secondary data from endoscopy’s reports. The balanced scorecard contains 4 measurements, such as financial approach, customer approach, internal process approach, and learning and growth approach. Results: The financial approach resulted that income from 2 types of patients (cash and insurance) were increased in 2013. The customer approach resulted a high satisfaction rate with mean 4.69 of 5 for patient satisfaction and the employee satisfaction increased in 2013 (mean: 3.88 of 5) and in 2010 (mean: 3.64 of 5). Internal process approach was measured using facilities and infrastructure discovered is increased too. Learning and growth approach resulted that accumulation of trainings, achievement of target of the trainings was increased.Conclusion: The achievement of bussiness plan has been evaluated using balanced scored card and showed that there is a balance on the financial approach, customer approach, internal process approach, and learning and growth approach.Keywords: business plan, digestive endoscopy center, balance scorecard